2022
DOI: 10.1111/1462-2920.15927
|View full text |Cite
|
Sign up to set email alerts
|

From gut to mud: dissemination of antimicrobial resistance between animal and agricultural niches

Abstract: With increasing reports on antimicrobial resistance (AMR) in humans, animals and the environment, we are at risk of returning to a pre-antibiotic era. Therefore, AMR is recognized as one of the major global health threats of this century. Antibiotics are used extensively in farming systems to treat and prevent infections in food animals or to increase their growth. Besides the risk of a transfer of AMR between the human and the animal sector, there is another yet largely overlooked sector in the One Health tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 153 publications
0
26
0
Order By: Relevance
“…Although ARGs developed in clinical and natural environments with different driving forces, the rapid evolution and spread of ARGs in the past decades were undoubtedly related to the utilization and excretion of antibiotics. In particular, antibiotics exert extensive selective pressures on microbes, which promote the amplification, inter/intracellular transfer, and mutation-based generation of ARGs in scenarios such as hospitals, farmlands, and sewage treatment plants . For instance, manure fertilizer and wastewater irrigation were considered to be the main anthropogenic sources of ARGs, while they are often associated with high antibiotic concentrations in agricultural systems. , However, such selective pressures are indeed uncommon for most natural environments in which antibiotic concentrations are generally lower than their estimated (or known) minimum selective concentrations in the laboratory, i.e., at ppb or even lower levels. , Instead, the physicochemical properties of the environmental interfaces and mixing effects of coexisting compounds have more profound impacts on the diversity and abundances of ARGs. Chen et al recently reported the shaping effects of soil aging on the development of the resistome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ARGs developed in clinical and natural environments with different driving forces, the rapid evolution and spread of ARGs in the past decades were undoubtedly related to the utilization and excretion of antibiotics. In particular, antibiotics exert extensive selective pressures on microbes, which promote the amplification, inter/intracellular transfer, and mutation-based generation of ARGs in scenarios such as hospitals, farmlands, and sewage treatment plants . For instance, manure fertilizer and wastewater irrigation were considered to be the main anthropogenic sources of ARGs, while they are often associated with high antibiotic concentrations in agricultural systems. , However, such selective pressures are indeed uncommon for most natural environments in which antibiotic concentrations are generally lower than their estimated (or known) minimum selective concentrations in the laboratory, i.e., at ppb or even lower levels. , Instead, the physicochemical properties of the environmental interfaces and mixing effects of coexisting compounds have more profound impacts on the diversity and abundances of ARGs. Chen et al recently reported the shaping effects of soil aging on the development of the resistome.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, antibiotics exert extensive selective pressures on microbes, which promote the amplification, inter/intracellular transfer, and mutation-based generation of ARGs in scenarios such as hospitals, farmlands, and sewage treatment plants. 12 For instance, manure fertilizer and wastewater irrigation were considered to be the main anthropogenic sources of ARGs, while they are often associated with high antibiotic concentrations in agricultural systems. 13,14 However, such selective pressures are indeed uncommon for most natural environments in which antibiotic concentrations are generally lower than their estimated (or known) minimum selective concentrations in the laboratory, i.e., at ppb or even lower levels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alternatively, antibiotic resistant bacteria or ARGs could have been introduced to the soil from external sources. This is common in soils exposed to livestock manure or sludge [9,18]. Moreover, the dispersal through unconventional sources such as birds can provide the initial seed for the microbial communities to spread AMR.…”
Section: Discussionmentioning
confidence: 99%
“…This is essential to achieve climate-change goals and concomitantly meet the dietary demands of 9 billion people by 2050. However, the build-up of antibiotic concentrations and ARG abundance in environmentally sustainable organic fertilisers, such as livestock manure and sewage sludge, permeates agricultural soils to spread AMR by altering the microbiome [1,9,13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although ARGs developed in clinical and natural environments with different driving forces, the rapid evolution and spread of ARGs in past decades were undoubtedly related to the utilization and excretion of antibiotics. In particular, antibiotics exert extensive selective pressures on microbes, so that signi cant ARG mobilization, horizontal transfer and mutation-based generation occur in scenarios such as hospitals, farmlands and sewage treatment plants (Jadeja and Worrich 2022). However, such selective pressures are indeed uncommon for most natural environments in which antibiotic concentrations were generally lower than their estimated (or known) minimum selective concentrations in the laboratory, i.e.…”
Section: Introductionmentioning
confidence: 99%